Igneous Rock Associations 14. The Volcanic Setting of VMS and SMS Deposits: A Review - Ross, Pierre-Simon; Mercier-Langevin, Pierre (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
Volcanogenic massive sulphide (VMS) deposits and seafloor massive sulphide (SMS) deposits have a spatial and genetic connection with contemporaneous volcanism. The control exerted by the volcanic succession (e.g. rock type, architecture and facies) on the nature and style of the ore and alteration (e.g. subsea-floor replacement vs. exhalative, or discordant vs. conformable) is significant, making it imperative to understand the local volcanology in developing better genetic and exploration models. Three VMS deposit groupings collectively represent a high proportion of cases: (1) deposits associated with complexes of submarine felsic domes, cryptodomes, lobe-hyaloclastite flows and/or blocky lavas, and their reworked equivalents; (2) deposits associated with thick piles of pumiceous felsic pyroclastic rocks, suggesting a caldera context; and (3) deposits associated with mafic volcanic footwalls and/or with sedimentary hosts, including significant deposits such as Windy Craggy (~300 Mt) in British Columbia. With regard to number (2) above, demonstrating the presence of a caldera in ancient successions can be difficult because silicic calderas tend to be large and exceed the limits of deposit-scale investigations. Furthermore, there is no consensus regarding what a large submarine caldera should look like, i.e., no accepted facies model exists showing the distribution of rock types. But without thick piles of pumiceous felsic pyroclastic deposits, arguing for a large submarine caldera is a challenge.